Sustainability Level of Management of â€œPondok Dadapâ€ Fish Auction Place to Support Marketing of Marine Fish in Sendangbiru, East Java - Zainal Abidin; Mimit Primyastanto (Sekolah Pascasarjana Universitas Brawijaya, 2017)
This research aims to analyze the level of sustainability management of fish auction place (TPI) Pondok Dadap. Methods of data analysis using the techniques of Multidimensional Scalling (MDS) through a RAPFISH approach. The results showed that the average index value of sustainability management of fish auction place (TPI)